Metabolomic strategies and biochemical analysis of the effect of processed Rehmanniae radix extract on a blood-deficient rat model - Yang-yang Wang; Ning Zhou; Zeng-fu Shan; Ying-ying Ke; Zhen Liu; Zhen-hui Liu; Wei-sheng Feng; Xiao-ke Zheng (BMC, 2022)
Abstract Background Rehmanniae Radix (RR), an herb with numerous pharmacological effects, is widely used in traditional Chinese medicine for the treatment of blood deficiency syndrome, either alone or in combination with other herbs. However, the mechanism by which processed Rehmanniae Radix (PRR) improves blood enrichment efficacy has not been clearly defined. Methods Ultra-performance liquid chromatography coupled to quadrupole time-of-flight mass (UPLC-Q-TOF/MS) and biochemical methods were combined to explore the hematopoietic functional mechanisms of PRR on blood deficiency in a rat model, as well as the potential active ingredient for blood enrichment efficacy. The pharmacological effects of PRR were evaluated on a rat blood deficiency model induced by cyclophosphamide in combination with 1-acetyl-2-phenylhydrazine. The blood routine index, including white blood cell (WBC), red blood cell (RBC), and platelet (PLT) counts, as well as hemoglobin (HGB) level, and the changing metabolite profile based on urine and serum were assessed. Nontargeted metabolomic studies, combined with biochemical analyses, were employed to clarify pharmacological mechanisms. Results PRR significantly increased the blood routine index levels and reversed the levels of SOD, GSH, and ATP. The PRR group was similar to the control group, as determined from the metabolic profile. All of the 60 biomarkers, representing the typical metabolic characteristics of the blood-deficient rat model, mainly involved energy metabolism dysfunction, the peripheral circulation system, and oxidative damage in the body. This improvement may be attributed to changes in polysaccharide and sixteen non-polysaccharide compounds in PRR, which were caused by processing RR with rice wine. Conclusions The strategies of integrated metabolomic and biochemical analyses were combined, revealing the biological function and effective mechanism of PRR.